2018
DOI: 10.3389/fphys.2018.00997
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Consumption of a Mediterranean-Like Dietary Pattern With Vitamin D3 Supplements Induced Small Scale but Extensive Changes of Immune Cell Phenotype, Co-receptor Expression and Innate Immune Responses in Healthy Elderly Subjects: Results From the United Kingdom Arm of the NU-AGE Trial

Abstract: Amongst the major features of aging are chronic low grade inflammation and a decline in immune function. The Mediterranean diet (MedDiet) is considered to be a valuable tool to improve health status, and although beneficial effects have been reported, to date, immunological outcomes have not been extensively studied. We aimed to test the hypothesis that 1 year of a tailored intervention based on the MedDiet with vitamin D (10 μg/day) would improve innate immune responses in healthy elderly subjects (65–79 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…Specifically, in Healthy Lifestyle in Europe by Nutrition in Adolescence study, adherence to a Mediterranean diet was associated with an attenuation in oxidative stress response in adolescents 45. Similarly, in the randomised controlled trial of European Project on Nutrition in Elderly People, adherence to a Mediterranean diet for 1 year was associated with significant changes in innate and adaptive immunity as measured by T cell degranulation, cytokine production and co-receptor expression 8. These results are further supported by a number of cross-sectional analyses of patients with immune-mediated disorders including CD and psoriasis demonstrating an inverse relationship between adherence to a Mediterranean diet and disease activity 9 46.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, in Healthy Lifestyle in Europe by Nutrition in Adolescence study, adherence to a Mediterranean diet was associated with an attenuation in oxidative stress response in adolescents 45. Similarly, in the randomised controlled trial of European Project on Nutrition in Elderly People, adherence to a Mediterranean diet for 1 year was associated with significant changes in innate and adaptive immunity as measured by T cell degranulation, cytokine production and co-receptor expression 8. These results are further supported by a number of cross-sectional analyses of patients with immune-mediated disorders including CD and psoriasis demonstrating an inverse relationship between adherence to a Mediterranean diet and disease activity 9 46.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings have plausible biologic mechanisms. Several dietary intervention studies have demonstrated significant changes in inflammatory markers, immune cell populations and response to oxidative stress with Mediterranean diet 8 45. Specifically, in Healthy Lifestyle in Europe by Nutrition in Adolescence study, adherence to a Mediterranean diet was associated with an attenuation in oxidative stress response in adolescents 45.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probands were enrolled in five European countries (Italy, Poland, France, the Netherlands, and the UK), and a 1-year Mediterranean-like diet was administered to the intervention subgroup. A comprehensive clinical and molecular characterization was performed at baseline and after the 1-year intervention, and results achieved so far in the framework of this study have demonstrated a beneficial effect of the Mediterranean-like diet on global cognition and episodic memory (Marseglia et al 2018), osteoporosis , immune function (Maijo et al 2018), and cardiovascular health , as well as on the proteasomal proteolysis (Athanasopoulou et al 2018). The NU-AGE study design (different countries with different dietary traditions and habits) and the large number of collected data allowed to evaluate the impact of relevant variables usually poorly investigated (age, sex, and ethnicity/genetics, as well as individual characteristics) on different parameters at baseline and after the intervention (Konz et al 2018;Marseglia et al 2018;Ostan et al 2018;Pujos-Guillot et al 2018;Santoro et al 2018Santoro et al , 2019Jennings et al 2019).…”
Section: Introductionmentioning
confidence: 90%
“…A significant association was observed between increased adherence to the NU-AGE MedDiet and enhanced global cognitive ability and episodic memory 17. Moreover, higher adherence has been shown to reduce the rate of bone loss in individuals with osteoporosis18 and to improve innate immune function,19 blood pressure and arterial stiffness 20. In the current study we have profiled the effect of the NU-AGE MedDiet on the gut microbial community of a subset of participants from the NU-AGE trial comprising 612 individuals (289 controls (145 men and 144 women) and 323 with the NU-AGE MedDiet (141 men and 182 women)).…”
Section: Introductionmentioning
confidence: 99%